2016
DOI: 10.1111/1346-8138.13381
|View full text |Cite
|
Sign up to set email alerts
|

Behçet's disease: A comprehensive review with a focus on epidemiology, etiology and clinical features, and management of mucocutaneous lesions

Abstract: Behc ßet's disease (BD) is a chronic, relapsing, inflammatory multisystem disease of unknown etiology. Oral ulcers, genital ulcers, cutaneous lesions, and ocular and articular involvement are the most frequent features of the disease. Mucocutaneous lesions are considered hallmarks of the disease, and often precede other manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
279
3
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(312 citation statements)
references
References 107 publications
5
279
3
8
Order By: Relevance
“…The association with HLA-B5 was first described by Ohno et al in 1973. Several studies confirmed the HLA-B51 association with BD and HLA-B51 is the strongest known genetic factor for BD [1]. The MHC region on chromosome 6p21 contains HLA and other essential genes in the immune response [14].…”
Section: Genetic Factorsmentioning
confidence: 91%
See 3 more Smart Citations
“…The association with HLA-B5 was first described by Ohno et al in 1973. Several studies confirmed the HLA-B51 association with BD and HLA-B51 is the strongest known genetic factor for BD [1]. The MHC region on chromosome 6p21 contains HLA and other essential genes in the immune response [14].…”
Section: Genetic Factorsmentioning
confidence: 91%
“…Several investigations have shown the association between HSV and BD. But, in some studies, this association could not detected [1,15,16]. Therefore, the role of HSV at the etiopathogenesis of BD is not clear.…”
Section: Infectious Agentsmentioning
confidence: 95%
See 2 more Smart Citations
“…Behcet's disease (BD) is a multi-systemic, inflammatory, and chronic disorder characterized by a triple-symptom complex of recurrent oral aphthous ulcers, genital ulcers, uveitis [1,2], and other diverse spectrum of clinical manifestations, including skin, joint, Central Nervous System (CNS), gastrointestinal, pulmonary, and cardiovascular system involvement, which are reported in addition to the major findings of this disorder. Cardiac involvement in BD is known as cardio-Behcet's disease that occurs in 7% to 31% of patients with BD, with a mortality rate of 20% [3].…”
Section: Introductionmentioning
confidence: 99%